(3GdJMbjbGJ GdMbjbjI aj GdCUhd GdYedjIs - (3MSf GdNGbGfjs
(3ChdgG (B:s
(3GdMeO ddg (B...(3deG aQZJ ef GdLRA GdKGfj ef JMQjQfG GdeJcad dCUd GdHQGAI hGdGTJZGd GdePchQ ef ajg HYO GfJgGA (B.. (3efLRjI GdYde GdELeGdj TQYJ aj GdGSJUMGH GdPj dGHO ddeLJO ef eYQaI ehGQOg (B...s
(3BNQgG (B:s
...(3jbOM aj GdebGe HdG QjH dChdj GdCagGe aJOHQ LjOG aEfg eJjf LOG hGddg GdYGde hdg GdMeO Ydi JdWag YdjfG HeG QVGg ef GdGJeGes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs